1996
DOI: 10.1046/j.1365-2125.1996.03246.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and pharmacokinetics of a new intrarectal quinine formulation in children with Plasmodium falciparum malaria

Abstract: 1Three groups of seven children aged 2–14 years with acute uncomplicated Plasmodium falciparum malaria received 12.8 mg kg−1 quinine gluconate by the intrarectal route (new cream formulation) or 8 mg kg−1 Quinimax (a Cinchona alkaloid combination) by the intramuscular or intravenous (4 h infusion) route every 8 h for 3 days. Clinical and parasitological status was similar in the three groups at enrolment. 2At 36 h, body temperature of all children of the three groups was returned to normal and remained so unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 5 publications
3
37
0
Order By: Relevance
“…The substitution of the hydrochloride for a gluconate salt and an increase in the pH value to 4.5 improve the local tolerance but may affect the extent of drug distribution (18). The kinetics profiles obtained after intravenous and intramuscular administrations are similar to those previously reported for hydrochloride salt (4,5). In contrast, after rectal administration of 8 mg/kg, the bioavailability of the gluconate form is higher than that previously observed with the more acidic formulations (3,5,6).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The substitution of the hydrochloride for a gluconate salt and an increase in the pH value to 4.5 improve the local tolerance but may affect the extent of drug distribution (18). The kinetics profiles obtained after intravenous and intramuscular administrations are similar to those previously reported for hydrochloride salt (4,5). In contrast, after rectal administration of 8 mg/kg, the bioavailability of the gluconate form is higher than that previously observed with the more acidic formulations (3,5,6).…”
supporting
confidence: 61%
“…We previously showed that intrarectal administration of various formulations of quinine was as effective as the currently used intramuscular treatment of childhood malaria (2,3). Nevertheless, a large interindividual variability was observed in quinine bioavailability and concentrations in blood according to the galenic formulation and the administered dose (2,4,6). Whatever rectal formulation is used, the drug may be extruded spontaneously without being noticed, leading to a decrease of clinical efficacy.…”
mentioning
confidence: 99%
“…Comparable results have also been reported by Barennes et al (1996) after treating falciparum malaria in children using 12.8 mg quinine gluconate/kg administered via the intrarectal, intramuscular or intravenous route: parasitaemia after 48 h was 7.4 ± 16%, 4.1 ± 4.2% and 2.2 ± 3.8%, respectively; all children were aparasitemic on day 7 (Barennes et al, 1996).…”
Section: Bioavailability Of Quinine After Single Dose Oral Administrasupporting
confidence: 80%
“…The artemisinin-based combinations, such as artesunate-amodiaquine (Adjuik et al, 2002) and artemether-lumefantrine (van Vugt et al, 2000), are currently the most advocated for treating African children with uncomplicated P. falciparum malaria. However, P. falciparum is also sensitive to quinine (Bjorkman, 1991;Bourée, 2006), and the available evidence reports that African strains of P. falciparum generally remain sensitive to quinine (Barennes et al, 1996;Henry et al, 2006;Pradines et al, 2006;Tinto et al, 2006;Quashie et al, 2007). Even though quinine resistance was first documented in 1910, P. falciparum sensitivity to quinine is still retained throughout the world (Deen et al, 2008), and more than half of the national malaria control programs in Africa still recommend monotherapy with oral quinine as second line treatment.…”
Section: Introductionmentioning
confidence: 96%
“…It can be administered orally, intramuscularly, or intravenously. However, the use of intramuscular QN in children may cause abscess, and therefore, this route of administration is discouraged [6]. As a result of its characteristic bitter taste, QN is preferably used in children in the form of syrup [7] but poorly prepared quinine syrups (QNSs) are subject to microbial contaminations, which may ultimately contribute to secondary bacterial infections, especially as the immune system of children is immature.…”
Section: Introductionmentioning
confidence: 99%